AKSESIBILITAS PEJALAN KAKI DI STASIUN YANG TERINTEGRASI DENGAN RENCANA TERHADAP KAWASAN BERKONSEP TOD (STUDI KASUS KAWASAN STASIUN TANJUNG BARAT) - Gading Kencono Aji; Sylvira Ananda; Tri Mulyono (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2019)
This research was conducted to assess the Level Of Service (LOS) pedestrian path around the Tanjung Barat Station area. In addition, to see in terms of comfort and security in reaching a TOD concept area. For this reason, a model of pedestrian design is needed so that track users can enjoy the pedestrian pathway feeling comfortable and safe. The results of this study indicate that the level of pedestrian service on the Tanjung Barat Raya road and on the road in Lenteng Agung raya: For the Tanjung Barat Raya road the LOS index is categorized as